Secondhand smoke exposure and pediatric brain development: resolving the paradox of BDNF dysregulation - Kenny Cantika Abadi; Maytia Pratiwisitha (Indonesian Society for Biochemistry and Molecular Biology, 2026)
Prenatal secondhand smoke (SHS) exposure is an increasingly recognized yet mechanistically undercharacterized risk factor for neurodevelopmental impairment. Brain-derived neurotrophic factor (BDNF) is essential for neurogenesis, neuronal survival, and synaptic plasticity, but prior studies report inconsistent findings on its regulation by tobacco-derived toxicants, a discrepancy that has impeded translational progress. This narrative review synthesized 52 sources retrieved from PubMed, Scopus, and Google Scholar (2000–2024), comprising predominantly rodent mechanistic studies together with a smaller set of human post-mortem and observational reports, addressing the differential regulation of the BDNF precursor (proBDNF) and its mature isoform (mBDNF) following tobacco or nicotine exposure. Because isoform-specific human evidence in the context of passive prenatal SHS exposure remains scarce, the mechanistic model proposed here is derived largely from active nicotine or cigarette smoke exposure paradigms and extrapolated to the SHS context, a lower-dose exposure that may differ quantitatively, and possibly qualitatively, in its effects. Within this scope, nicotinic acetylcholine receptor activation and oxidative stress appear to upregulate total BDNF transcription, while the post-translational proteolytic conversion of proBDNF to mBDNF, mediated by furin, matrix metalloproteinases, and the tPA/plasmin system, is concurrently impaired. We propose, as a hypothesis requiring direct empirical testing rather than an established conclusion, that this imbalance redirects neurotrophic signaling from the pro-survival TrkB pathway toward the pro-apoptotic p75NTR cascade, and that it is plausibly associated with the cognitive, attentional, and behavioral difficulties reported in some prenatally exposed children. We further propose that the proBDNF/mBDNF ratio, rather than total BDNF concentration alone, may represent a more functionally relevant candidate biomarker, although its clinical utility remains unproven pending prospective validation and clarification of the peripheral-central BDNF correlation. Collectively, this model offers a testable mechanistic framework, rather than a settled explanation, for the neurodevelopmental consequences of in utero SHS exposure.